Identification of Stem-Like Cells in Atrial Myxoma by Markers CD44, CD19, and CD45 - Xianghe Song; Danni Liu; Jian Cui; Manqian Zhou; Hui Wang; Na Liu; Xin Qi; Zongjin Li (Hindawi Limited, 2016)
Atrial myxoma is the most frequent tumor arising mainly in atrial septum and its origin remains uncertain. It has been reported that a subpopulation of stem-like cells are present in benign tumors and responsible for tumor initiation and maintenance. In this study, we investigated whether stem-like cells could contribute to the atrial cardiac myxoma. Immunohistology data confirmed that a population of cells bearing the surface markers CD19, CD45, and CD44 resided in a mucopolysaccharide-rich matrix of myxoma. Moreover, we isolated myxoma cells with phase-bright culture method and confirmed that myxoma derived cells express robust level of CD19, CD45, and CD44. Furthermore, the pluripotency of this population of cells also was validated by cardiomyocytes and smooth muscle cells differentiation in vitro. Our results indicate that primary cardiac myxoma may arise from mesenchymal stem cells with the ability to generate tumors with multilineage differentiation. In conclusion, this study for the first time verified that stem-like cells are present in atrial myxoma and this population of cells may have the capacity for myxoma initiation and progression.